2019
DOI: 10.3389/fpls.2019.00572
|View full text |Cite
|
Sign up to set email alerts
|

Light Availability and Patterns of Allocation to Reproductive and Vegetative Biomass in the Sexes of the Dioecious Macrophyte Vallisneria spinulosa

Abstract: Environmental changes, e.g., eutrophication, in aquatic ecosystems can greatly alter light available to submerged macrophytes. In dioecious plants, given potential for sex-specific differences in resource requirements (i.e., high-carbon for seeds vs. high-nitrogen for pollen), females and males are expected to divergently adjust allocations toward resource acquisition structures when resources are limited during growth. Here, Vallisneria spinulosa was used as a representative dioecious s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Submerged macrophytes normally adapt to low light availability in water column by one of two distinct strategies – elongating shoot toward water surface to alleviate low light stress or enhancing low light tolerance through photosynthetic adjustments (Riis et al, 2012; Chen et al, 2016). Yet relatively fewer studies exist dealing with the variation in plant reproductive traits (Li et al, 2017, 2018), and even fewer studies have been conducted to further understand patterns of sexual dimorphism in dioecious macrophytes compared to their terrestrial relatives (Dorken and Barrett, 2004; Li et al, 2019b). Reproductive strategies influence the response of populations to environmental variation (Dorken and Barrett, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Submerged macrophytes normally adapt to low light availability in water column by one of two distinct strategies – elongating shoot toward water surface to alleviate low light stress or enhancing low light tolerance through photosynthetic adjustments (Riis et al, 2012; Chen et al, 2016). Yet relatively fewer studies exist dealing with the variation in plant reproductive traits (Li et al, 2017, 2018), and even fewer studies have been conducted to further understand patterns of sexual dimorphism in dioecious macrophytes compared to their terrestrial relatives (Dorken and Barrett, 2004; Li et al, 2019b). Reproductive strategies influence the response of populations to environmental variation (Dorken and Barrett, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental factors (e.g., plant type, leaf shape, treatment method, experiment duration and percentage, and experimental end season) have been shown to affect the growth responses of plants to light reduction [3,30,74,75]. We found that the lnRRs of RGR were significantly negative for plants grown from shoots and seedlings but nonsignificantly positive for those grown from mature plants at the beginning of the experiment (Figure 1b), which might be related to more carbon storage in mature plants leading to greater adaptability.…”
Section: Factors Influencing the Responses Of Rgr And Other Traits To...mentioning
confidence: 99%
“…For instance, submerged macrophytes could ease low light stress via growth-related and physiological trait adjustments (e.g., shoot length, biomass allocation, and leaf photosynthesis parameters) to optimize light utilization and increase survival probability [27][28][29]. Thus, functional traits are considered vital drivers in regulating the growth strategies of submerged macrophytes [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication arising from N and P enrichments is supposed to reduce light availability by promoting the growth of phytoplankton and periphyton, thereby resulting in a shading effect upon submerged macrophytes (Roberts et al, 2003;Sayer et al, 2010;Olsen et al, 2015). Furthermore, the allocation of limiting resources, as an important adaptive strategy for how plants respond to different and changeable environments, reflects the influences of evolutionary history, environmental stresses and trade-offs of functional traits (Xie et al, 2005;Kerkhoff et al, 2006;Dulger et al, 2017;Scartazza et al, 2017;Li et al, 2019). To maximize their multiple functions, namely growth, reproduction, and nutrient storage of plants, plants need to rebalance the allocation of elements across organs under various environmental stresses (Schreeg et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient allocation strategies among organs may reflect the interplay between plants and their ambient environments, because plants can coordinate different organs to satisfy the nutritional requirements of various functions with respect to the allocation of limited nutrients and adaptation to a changing environment (Liu et al, 2010). According to previous studies, plant species as well as the availability of light resources and nutrient can significantly influence the nutrient concentrations of a single organ (Xing et al, 2013;Grasset et al, 2015;Su et al, 2016;Dulger et al, 2017;Li et al, 2017Li et al, , 2019Velthuis et al, 2017). Accordingly, we hypothesize that nutrient allocation among organs differs not only among growth forms but also changes with key environmental factors.…”
Section: Introductionmentioning
confidence: 99%